PENINGKATAN KUALITAS PRODUK DUPA BAGI MITRA IBM DUPA DI DESA DALISODO KABUPATEN MALANG - Wulandari, Wahju; Sodik, Sodik (Direktorat Penelitian dan Pengabdian Kepada Masyarakat, 2018)
The goal to be achieved in this IbM activity is to produce quality incense products and according tostandard so that prices can compete in the market. Does not cause air pollution in the productionprocess. While the specific targets to be achieved are quality incense and incense products morestandard with higher selling value. The action to be taken is: the manufacture of automatic incensemachine with the capacity of 15.080 pcs / minute, so that the production process can be done quickly,large scale and meet market demand. The output generated in the form of automatic incense machinecapable of increasing the production capacity of 100kg per person per day and the production processfaster so that the labor wage earned per day becomes larger Rp. 150.000,